2018
DOI: 10.5815/ijieeb.2018.05.02
|View full text |Cite
|
Sign up to set email alerts
|

Using Publications Linked Open Data to Define Organizational Policies

Abstract: Researchers around the world are publishing their scientific research results in different forms such as books, journal articles, reference works and project reports. Publishers of these scientific documents usually describe them by using metadata for organizational purposes. This metadata provides a rich information about scientific documents that can be used for analysis purposes such as measuring the impact of researchers and research centers. It can also be used to find scientific documents published in do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The goal of SPedia is to facilitate a semantic-based search to allow users to pose smart and complex queries and overcome the limitations of traditional keyword-based searching by creating a SPARQL endpoint to query the dataset ( Ahtisham & Aljohani, 2016 ). The authors demonstrated how SPedia can be used to analyze trends in joint publications and research collaborations ( Ahtisham, 2018 ). The results retrieved from the SPedia knowledge base using SPedia SPARQL Endpoint enables the performance of both individual researchers and organizations to be analyzed.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The goal of SPedia is to facilitate a semantic-based search to allow users to pose smart and complex queries and overcome the limitations of traditional keyword-based searching by creating a SPARQL endpoint to query the dataset ( Ahtisham & Aljohani, 2016 ). The authors demonstrated how SPedia can be used to analyze trends in joint publications and research collaborations ( Ahtisham, 2018 ). The results retrieved from the SPedia knowledge base using SPedia SPARQL Endpoint enables the performance of both individual researchers and organizations to be analyzed.…”
Section: Related Workmentioning
confidence: 99%
“…The results retrieved from the SPedia knowledge base using SPedia SPARQL Endpoint enables the performance of both individual researchers and organizations to be analyzed. This process can help decision makers set future research directions ( Ahtisham, 2018 ). Moreover, SPedia is the first step toward achieving an LOD cloud of scholarly documents by well-known publishers such as Springer.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations